Association Between Platelet-Albumin-Bilirubin Grade and the 30-Day Mortality in Patients with Acute Respiratory Distress Syndrome: Evidence from the MIMIC-IV Database - Dandan Ye; Wei Jiang; Deming Gu (Balkan Medical Journal)
Background: The platelet-albumin-bilirubin (PALBI) grade is a comprehensive assessment index of liver function. Liver dysfunction is a key determinant of the pathogenesis and resolution of acute respiratory distress syndrome (ARDS), which affects the prognosis of patients. Aims: To evaluate the association of PALBI grade with the risk of 30-day mortality in patients with ARDS. Study Design: Retrospective cohort study. Methods: Univariate and multivariate Cox proportional hazards models were used to evaluate the association between PALBI grade and the 30-day mortality in patients with ARDS; results were described as hazard ratios (HRs) and 95% confidence intervals (CIs). This association was further assessed by subgroup analyses stratified based on age, sex, and complications. Results: A total of 2,841 patients with ARDS were included, of whom, 703 (24.74%) died within 30 days. After adjusting all covariates, a higher PALBI grade was associated with higher odds of 30-day mortality (HR: 1.55, 95% CI: 1.05-2.29). High PALBI grade was related to higher odds of 30-day mortality in patients with ARDS aged ≥ 65 years (HR: 2.30, 95% CI: 1.06-5.01), males (HR: 2.10, 95% CI: 1.29-3.44), without sepsis (HR: 1.71, 95% CI: 1.11-2.64), without pneumonia (HR: 1.86, 95% CI: 1.19-2.91), and without any history of chronic obstructive pulmonary disease (HR: 1.93, 95% CI: 1.28-2.91). Conclusion: The PALBI grade was positively associated with 30-day mortality in patients with ARDS. The present study provides a reference for risk stratification management of patients with ARDS to improve short-term prognosis.